Hematopoietic Stem Cell Transplantations for Primary Immune Deficiencies: 3 Decades of Experience From a Tertiary Medical Center. Issue 5 (July 2015) - Rousso, Sharon Z.; Shamriz, Oded; Zilkha, Amir; Braun, Jacques; Averbuch, Diana; Or, Reuven; Weintraub, Michael; Revel-Vilk, Shoshana; Stepensky, Polina
Abstract : Hematopoietic stem cell transplantation (HSCT) remains the leading treatment for the majority of severe primary immune deficiency (PID). This study aims to analyze changes in outcome over time. We conducted a retrospective analysis of HSCT in children with PID in a tertiary medical center over the period of 1983 to 2012. We identified 93 children with PID with a median follow-up of 3.6 years (range, 29 d to 21.2 y) after HSCT. The 2-year survival rates after HSCT for children with severe combined immune deficiency, hemophagocytic lymphohistiocytosis/lymphoproliferative disease, Wiskott-Aldrich syndrome, granulocyte defect, and undefined PID were 65.7%±6.8%, 80%±10.3%, 83.3%±15.2%, 75%±12.5%, and 25%±21.7%, respectively. Survival was associated with year of HSCT and matching. The hazard ratio (HR) (95% CI) for HSCT done in 1983 to 1999 compared with 2000 to 2012 and for matched (related and unrelated) compared with mismatched donor were 2.14 (0.99 to 4.653) and 3.07 (1.46 to 6.4), respectively. Survival was not associated with age, sex of the recipient, underlying PID, conditioning regimen, and presence of acute graft-versus-host disease. After adjustment to the underlying PID, donor and use of fludarabine-based conditioning, the HR (95% CI) for HSCT from the year 2000 was 4.69 (range, 1.4 to 15.45). Advances in HSCT over time have improved the survival of children with PID.